Trivium 21c preparing young people for the future with lessons from the past - Robinson, Martin (Independent Thinking Press, 2013)
From Ancient Greece to the present day, Trivium 21c explores whether a contemporary trivium (Grammar, Dialectic, and Rhetoric) can unite progressive and traditionalist institutions, teachers, Read more...